Diagnosis Kesulitan Belajar Siswa Di Sekolah - Hapni Madini; Atika Azharo; Dina Rahmah Wati; Imam syafiq (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to describe and reveal data about the diagnosis of student learning difficulties at school and the teacher's efforts to identify the types and characteristics, as well as the factors that cause students to experience difficulties in learning. This research uses a qualitative research approach with a library research approach obtained from books, literature, articles, journals, and sites on the internet that are related to the research conducted. The results of the study show that learning difficulties are defined as obstacles to children in learning who have difficulty learning to read, understanding every learning the child cannot develop and receive the information obtained properly so that it affects the child's learning achievement. Factors that cause students to experience difficulties in learning are 2, namely internal factors which include psycho-physical disorders of students both in cognitive, affective, psychomotor aspects and external factors including family, school and community environments. Efforts made by teachers to overcome students' learning difficulties can make various strategic efforts involving identification, diagnosis, intervention, providing assistance and collaboration. In this effort, it is important for teachers to continuously improve their professional competence, especially in recognizing and dealing with various types of learning difficulties.